Editorial for Special Issue "Exclusive Papers of the Editorial Board Members of Oral" - Giuseppina Campisi (MDPI AG, 2024)
In 2022, the World Health Organization (WHO) released a landmark report on oral health, emphasizing the staggering global prevalence of oral disorders, which affect approximately 3 [...]